1996
DOI: 10.1007/bf00228629
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral displacement of lower limb evokes bilateral EMG responses in leg and foot muscles in standing humans

Abstract: During upright stance, foot dorsiflexion induced by the movement of a supporting platform elicits a short- (SLR) and a medium-latency response (MLR) in both the soleus and the flexor digitorum brevis muscles; foot plantarflexion elicits a MLR in the tibialis anterior. The SLR is the counterpart of the stretch reflex, but no general agreement exists about the origin of the MLR, though recent results suggest that it is transmitted through group II afferent fibres. Animal studies have shown that group II fibres i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 27 publications
2
38
0
4
Order By: Relevance
“…Recent studies involving healthy subjects have demonstrated that the degree of plantar flexor activity during propulsion depends on the degree of muscle activity 9 and on the magnitude of the ground reaction force 10 of the contralateral limb during heel strike. This interlimb relation observed during step-to-step transition of unimpaired walking 9,10 , and also in standing-related tasks 11,12 , can be justified by the bilateral influence of group II fibres on spinal interneurons 13 and by the importance of vestibulo-and reticulo-spinal pathways on group II fibres 14 .…”
Section: Introductionmentioning
confidence: 86%
“…Recent studies involving healthy subjects have demonstrated that the degree of plantar flexor activity during propulsion depends on the degree of muscle activity 9 and on the magnitude of the ground reaction force 10 of the contralateral limb during heel strike. This interlimb relation observed during step-to-step transition of unimpaired walking 9,10 , and also in standing-related tasks 11,12 , can be justified by the bilateral influence of group II fibres on spinal interneurons 13 and by the importance of vestibulo-and reticulo-spinal pathways on group II fibres 14 .…”
Section: Introductionmentioning
confidence: 86%
“…In fact, experiments on interlimb coordination of leg muscle activation have confirmed that unilateral leg displacement during gait evokes a bilateral response pattern, with a similar onset in both sides 3,4 but only when both limbs are performing a supportive role 5,6 . This is consistent with the evidence that a large majority of midlumbar interneurones recipient from group II input are influenced by afferent fibres from both ipsilateral and contralateral sides 7 and by vestibulo-and reticulo-spinal pathways 8 , and with the importance given to medium latency response from group II to feedback in the stance phase of gait 9 .…”
Section: Introductionmentioning
confidence: 97%
“…A minimal H reflex was considered when a consistent small H reflex was obtained for each stimulus pulse applied every 10 s. The stimulus pulse amplitude was set to 75% of the intensity required for a minimal soleus H reflex response to a single pulse. This value was smaller than what has been used in other studies 6,7,22 to avoid discomfort and to activate mainly large diameter sensory fibers. The sensation was perceived as an intense but painless vibration.…”
Section: Experimental Apparatus and Data Analysismentioning
confidence: 71%
“…The flexor digitorum brevis (FDB) is a foot muscle that serves as a physiological extensor during quiet stance because its contraction acts against the force of gravity 2 . Some studies [3][4][5][6][7][8] have indicated that FDB activity is highly correlated with the position of the body's center of mass, suggesting that stabilization is among its functions. In addition, FDB activity is highly correlated with the soleus EMG pattern during upright posture, which may either be due to common descending commands that act on both MN pools or to common innervations of these pools by each muscle's afferents 3,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation